Classics a very short introduction - Beard, Mary, 1955-; Henderson, John, 1949 June 12- (Oxford : Oxford University Press, 2000)
This 'Very Short Introduction to Classics' links a haunting temple on a lonely mountainside to the glory of ancient Greece and the grandeur of Rome, and to Classics within modern culture - from Jefferson and Byron to Asterix and Ben-Hur.
Originally published: 1995.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Classical literature -- History and criticism; Civilization, Classical